An approach to analyzing shippers' transportation management organization - Tim Brilka; Uwe Clausen (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: The purpose of this article is to present an approach to analyzing the organizational design of shippers' transportation management from a process perspective. Methodology: The proposed analysis approach is based on a comprehensive literature review on transportation management. The literature is categorized by horizontal, vertical, and internal organizational design strategies as well as process levels. Findings: The literature review reveals organizational design strategies and processes of transportation management. Furthermore, by transferring the results into an approach to analyzing the organizational design of a transportation management, it is shown that processes are shaped by organizational design strategies, which can lead to a variety of process variants. Each of these process variants, in turn, influences the performance of a transportation management organization. Originality: The revealed organizational design strategies and processes contribute to explanation-oriented and design-oriented research in the context of transportation management. The proposed analysis approach further provides a methodological contribution for shippers dealing with the optimization of their transportation management.
urn:nbn:de:gbv:830-882.0162330; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; HICL and Practice; Excellence in Logistics and Supply Chain Management